(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The present investigation concerns with the developments of hydrodynamically balanced tablets of cefixime trihydrate were designed to prolong the gastric residence time after oral administration and thereby increasing drug bioavailability. Materials and Methods: Floating tablets of cefixime trihydrate were prepared by direct compression using hydrophilic rate controlling polymers such as different grades of hydroxypropyl methylcellulose (HPMC) (k100 and 15M), xanthan gum, and ethyl cellulose. Buoyancy was achieved by adding an effervescent mixture of sodium bicarbonate and anhydrous citric acid and along with the binder and diluents. Results and Discussion: The kinetic study results suggested that the drug was released by Fickian diffusion mechanism for the developed floating matrix tablet formulations of cefixime trihydrate. The optimized formulation composed of 15% w/w xanthan gum exhibited 98.71Â±0.2% drug release within 12 h and the tablets remain floated for <12 h. Fourier transform infrared and differential scanning calorimetry studies were performed for pure drug and its physical mixture with polymer blends showed that no polymeric change interaction was occurred during manufacturing of tablet, and there is no significant change in in vitro dissolution pattern after storage at 40Â°C/75% R.H for 3 months for their stability studies.